1965
DOI: 10.1126/science.147.3659.754
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of DNA from Kinetoplasts of Leishmania enriettii

Abstract: The DNA of Leishmania enriettii can be separated by equilibrium sedimentation in cesium chloride into a major band of density 1.721 and a minor component of density 1.699. DNA from isolated kinetoplasts of this protozoan was identified as the less dense minor component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1966
1966
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…The impermewbility s f the kinetoplast membranes to exogenous DNAase is in agreement with studies on Neurosporu mitochondria( 11 ) and on water-lysed ghosts of Leishmania enrielti ( 6).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The impermewbility s f the kinetoplast membranes to exogenous DNAase is in agreement with studies on Neurosporu mitochondria( 11 ) and on water-lysed ghosts of Leishmania enrielti ( 6).…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, it has been found that none Olf the species of the Merrillosphaera section has protoplasmic connections in mature coenobia. This is one of the most marked structural differences between Euvolvox and Merrillosphaera (6). However, notwithstanding such a difference, no marked difference in the swimming pattern of the 2 coenolbia has ever been seen.…”
Section: Biological Laboratory Kansai Medical School Hirakata Citymentioning
confidence: 91%
“…Electron micrographs (19,11,25,30), electron microscope radio- autographs (1,22,10), and the resistance of mitochondrial DNA to DNase digestion in cell homogenates (7,16,23,29) all indicate that the DNA is within the matrix area of mitochondria. Results obtained with CsC1 density gradient centrifugation indicate that mitochondrial DNA often has a different base ratio than nuclear DNA from the same cell (7,2,16,17,23,26 (17,24,23) and increase in optical density (26,23) when heat-denatured. This indicates that this DNA is double stranded.…”
Section: Discussionmentioning
confidence: 99%
“…Another problem closely related to the morphologic and physiologic transformation of the brucei-subgroup trypanosomes is the origin of kinetoplastic DNA. As evidenced by its morphologic (70) as well as by its biochemical and biophysical properties ( 13,64,65,69,85), this substance differs in its base composition from nuclear DNA, and it has been suggested (64,65) that its biosynthesis, unlike that of nuclear DNA, involves exogenous rather than endogenously synthesized purines. Altho the nuclear origin of kinetoplastic DNA has been postulated on the basis of 2 isolated electronmicrographs( 9,62) and has been supported by analogous Occurrences in yeast ( 56), there is no categorical evidence for its origin, and the analogy between metabolic changes and mitochondria1 transformations in trypanosomes (see above) and in yeast(for pertinent references see 36) may be more apparenlt than real(96).…”
mentioning
confidence: 99%